Unveiling radio coverage of Muslim women. - Posetti, Julie (Radio Journal: International Studies in Broadcast & Audio Media, 2008)
With renewed calls for the banning of the Burqa in the United Kingdom and Australia triggered by French President Nicolas Sarkozy's push for a ban, the representation of Muslim women, and particularly coverage which focuses on the, wearing of the veil,1 is once again an important issue in media analysis in this post-September 11 world. If radio is to some extent a 'blind' medium, where visual appearance is less important, we can ask if the representation of this group is in anyway significantly different on radio than other media. However, there have been few detailed studies of the issue. This article seeks to address the gap in analysis of radio coverage of Muslim women by examining their representation on the flagship radio current affairs programmes produced by the Australian Broadcasting Corporation (ABC). The case study presented here highlights the strengths and weaknesses of reportage of Muslim women in sound broadcasting. The author also offers some reflections on the implications of the study for the identification of future best journalism practice for radio coverage of minorities.